Bond stress distribution along CFRP strengthened RC beam - Trombeva Gavriloska, Ana; Lazarevska, Marijana; Cvetkovska, Meri; knezevic, Milos (Drustvo gradjevinskih konstruktera Srbija, 2018)
A large number of existing RC structures exhibit non adequate performance in terms of diminished bearing capacity and there is a need of post strengthening during their service life. The aim of the presented work was to numerically assess the influence of the presence of discontinuous zone upon overall response of the CFRP strengthened RC beam.
Keywords: bond stress distribution, CFRP